Efficacy of zinc in amelioration of aflatoxicosis in broiler chickens - SHARMA, MAMTA; SINGH, RAM; MANDAL, A B; GUPTA, VIVEK PRASAD (The Indian Journal of Animal Sciences, 2014)
In the present study the effect of zinc supplementation in ameliorating aflatoxicosis in broiler chickens was studied. Day-old broiler chicks (240) were divided into 6 treatment groups containing 5 replicates of 8 birds each (T1–control; T2- T1+ 250 ppb AFB1; T3- T1+ 20 mg Zn/kg; T4- T1+ 40 mg Zn/kg; T5– T2 + 20 mg Zn/kg; T6- T2 + 40 mg Zn/kg diet) and the experiment was conducted from day 1 to 42 days of age. During overall growth period (0–6 weeks), the weight gain of broilers in control (T1) was 1,341.90 g as against 1,123.43 g in aflatoxin (AF) fed group (T2) which was significantly lower. The body weight gain (BWG) in T3, T4 and T6 was statistically similar to that of control, however the BWG in T5 was higher than T2 but could not match with that of control (T1). Supplementation of 40 mg Zn/kg in AF contaminated diet significantly improved the BWG. The overall feed intake (FI) in groups (T3, T4, T5 and T6) was statistically similar to that of control group, however, the FI in group T2 was significantly reduced compared to control. The overall FCR in AF fed group (T2) was higher than that of control. The FCR in all other treatment groups was statistically similar to that of control. AF increased the relative weights of liver and spleen while decreased in weight of bursa. These effects of AF were ameliorated by supplementation of 40 mg Zn/kg feed. It was concluded that aflatoxin contamination (250 ppb) in broiler diet impaired the performance in terms of body weight gain, feed intake and feed conversion efficiency and relative organ weights. Supplementation of 40 mg Zn/kg to the aflatoxin contaminated diet ameliorated the ill effects of aflatoxicosis on performance of the birds.